Pseudo-Meigs syndrome: a rare presentation of pedunculated fibroid - Dubey, Sunita; Goel, Poonam; Pandey, Nidhi; N., Pavithra H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Serosal fibroid of uterus are usually asymptomatic but rarely; it may present with atypical symptoms to simulate malignancy and needs extensive evaluation. Authors are reporting a case of 26 years old P1L1 female with history of asymptomatic multiple intramural fibroids since 6 years came with complained of progressively increasing abdominal distension and mild pain abdomen from 2-3 months. On evaluation, she had ascites, pleural effusion and raised Ca-125. MR imaging of pelvis revealed moderate ascites and pedunculated serosal fibroid in addition to intramural fibroids with normal bilateral ovaries. She was evaluated to rule out uterine sarcoma and tuberculosis but diagnosis of them could not be established. Finally, conclusion of Pseudo-Meigs syndrome was made. Myomectomy of single pedunculated fibroid relieved her symptoms. Though, subserosal fibroids are benign in pathology, timely surgery is must to avoid morbidity and mortality owing to massive ascites and pleural effusion.